Block copolymer compatibilizer containing semiconductor and elastomer fragments and preparation, separation and application thereof

By designing the block copolymer "compatibilizer", combining the π-π action and similar compatibility principle, the problem of incompatibility of electrical and mechanical properties in flexible stretchable semiconductor materials is solved, and efficient charge transport and excellent Tensile properties extend the service life of the material.

CN119285966APending Publication Date: 2025-01-10BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411414633.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The electrical and mechanical properties of existing flexible stretchable semiconductor materials are incompatible, resulting in a decrease in charge transfer performance of the material during the tensile release cycle and a short service life.

Method used

Design a block copolymer "compatibilizer" containing semiconductor and elastomer fragments, which is synthesized through polycondensation reaction and metal coupling reaction, combining π-π action and similar similarity principles to improve charge transport efficiency and fatigue resistance , realizes the material with high efficiency charge transport and excellent tensile properties.

Benefits of technology

The organic unity of the electrical and mechanical properties of flexible stretchable electronic materials is achieved, and the service life of the material is extended. The electrical properties of the blended film remain stable after cyclic stretching of 1000 times under 100% strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285966A_ABST
    Figure CN119285966A_ABST
Patent Text Reader

Abstract

The invention discloses a block copolymer compatibilizer containing a semiconductor polymer and an elastomer fragment, and preparation, separation and application thereof. The structural formula of the compatilizer is as shown in formula 1. The preparation method comprises the following steps: synthesizing a semiconductor conjugated polymer by utilizing a polycondensation reaction mechanism, carrying out end capping on the semiconductor conjugated polymer through a metal coupling reaction (Stille reaction or Suzuki reaction), and polymerizing with an elastomer flexible segment to prepare a segmented copolymer compatilizer containing semiconductor and elastomer segments at the same time. On the basis of a'compatibility 'strategy, organic unification of electrical properties and mechanical properties of the flexible stretchable electronic material can be realized, and the prepared block copolymer'compatilizer' can effectively link a conjugated polymer and an elastomer polymer through a similar intermiscible principle to prepare a composite active layer with efficient charge transport and excellent tensile properties. And a flexible and stretchable field effect transistor is constructed. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor conjugated polymers and elastomeric polymers, and specifically relates to a block copolymer "compatibilizer" comprising semiconductor polymers and elastomeric segments, and the preparation, separation and application thereof. Background Art

[0002] Flexible and stretchable electronics is a disruptive science and technology based on a high degree of cross-disciplinary integration. It can break through the intrinsic limitations of classical silicon-based electronics and provide innovative guidance for the design and integration of devices in the post-Moore era, energy revolution, medical technology reform, and other upgrades. It is an important strategic opportunity for my country's independent innovation to lead the development of future industries. Although the field of flexible and stretchable electronics has achieved rapid development in recent years, as an emerging field, it still faces many problems and challenges, especially the contradiction between the severe lack of development of stretchable electronic materials and the growing application demand of next-generation information functional devices.

[0003] For the basic components of flexible electronic circuits, field effect transistors (FETs), the research on the most critical active layer, stretchable semiconductors, is relatively lagging and its performance is average, which seriously restricts the development of stretchable transistors and integrated circuits. In order to solve these problems, researchers have made a lot of efforts, such as adjusting the molecular weight of conjugated polymers, introducing hydrogen bonds in the main chain or side chain of conjugated polymers, increasing the donor-acceptor torsion angle of conjugated polymer segments, and physically blending conjugated polymers with elastomers. Although these works have made some progress, most of them are completed by partially losing electrical properties to enhance mechanical properties. Therefore, designing high-performance stretchable semiconductor materials is a major challenge and difficulty in constructing flexible and stretchable electronic circuits, especially designing a flexible and stretchable electronic material with excellent mechanical flexibility and good electrical properties.

[0004] Flexible and stretchable electronic materials with excellent mechanical flexibility and good electrical properties mean that the charge transfer performance of the material is not affected during the continuous stretching and releasing cycle, which helps to improve the service life of the material. Therefore, it is necessary to design and prepare such flexible and stretchable materials with both mechanical and electrical properties. Summary of the invention

[0005] In response to the problem of incompatibility between electrical and mechanical properties in flexible stretchable semiconductor materials in the prior art, the present invention introduces the concept of "compatibilizer" for the first time in the preparation of stretchable semiconductor materials from the perspective of molecular design and material processing technology, that is, designing and synthesizing polymers with both conjugated rigid and flexible segments as a bridge connecting the semiconductor polymer and the flexible elastomeric polymer chain; wherein the rigid segments can be connected to the conjugated polymer units through π-π interaction, thereby ensuring effective electrical links between each aggregation state and improving the charge transport efficiency; on the other hand, the flexible segments can be entangled with the elastomeric polymer through the "like dissolves like" principle, enhancing the interaction between the conjugated polymer and the elastomeric polymer, reducing irreversible sliding between chains, and preventing irreversible plastic deformation during strain, thereby improving the elasticity and fatigue resistance of the material, and greatly extending the service life of the stretchable semiconductor material.

[0006] The present invention provides a method for preparing, separating and applying a block copolymer "compatibilizer" containing semiconductor and elastomer segments. By using the polycondensation reaction mechanism, a semiconductor conjugated polymer is first synthesized, and then the semiconductor polymer is capped by a metal coupling reaction (Stille reaction or Suzuki reaction), and then polymerized with an elastomer flexible segment obtained by anionic polymerization to prepare a block copolymer "compatibilizer" containing both semiconductor polymer and elastomer segments. At the same time, the process includes separating and purifying such block copolymer "compatibilizer" by column chromatography, which provides a simpler and more efficient strategy for separating and purifying polar polymers and non-polar polymers. Based on the "compatible" strategy, the organic unity of electrical and mechanical properties of flexible and stretchable electronic materials can be achieved, and the prepared "compatibilizer" can effectively connect conjugated polymers and elastomeric polymers through the principle of similar dissolution, prepare a composite active layer with both efficient charge transport and excellent stretching properties, and construct a flexible and stretchable field effect transistor, develop an integrated intrinsic stretchable electronic system, expand its application in the new generation of information devices such as wearable devices and electronic skin, and provide a good foundation for its commercialization. Composite semiconductor films were prepared by blending different proportions of "compatibilizers" with conjugated polymers and elastomeric polymers, and their mechanical and electrical properties were studied. The prepared flexible and stretchable device can be stretched 1000 times under 100% strain in subsequent cyclic stretching tests without reducing electrical properties, which greatly extends the service life of the stretchable device.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a block copolymer "compatibilizer" comprising semiconductor and elastomeric segments.

[0009] The structural formula of the "compatibilizer" is shown in Formula 1:

[0010]

[0011] In the structural formula 1, the semiconductor fragment refers to different conjugated polymer fragments synthesized by coupling polymerization reaction, including but not limited to: diketopyrrolopyrrole conjugated polymers, isoindigo conjugated polymers, naphthaleneimide conjugated polymers, and peryleneimide conjugated polymers;

[0012] Preferably, the A1 and A2 monomers are each independently selected from any structure of Formula 2 and structural units with similar functions expanded on the basis of this structure; wherein n in the semiconductor fragment is the number of A1-A2 repeating units, which is an integer ranging from 10 to 1000.

[0013] Preferably, the Ar unit is a group for terminating a semiconductor, including but not limited to: a thiophene group, a thienothiophene group, a dithiophene group, a benzene group, a diphenyl group, a naphthyl group, an anthracene group, and the like.

[0014] In the structural formula 1, the elastomer segment is polymerized by flexible units and rigid units; wherein R1, R2, R3, R4, R5, R6, and R7 are each independently selected from hydrogen, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, an alkoxy group, or an alkylthio group; the halogen atom includes F, Cl, Br, and I, and the alkyl group is a C1-C20 alkyl group.

[0015] The content of the elastomer segment accounts for 20-80wt% of the total amount of the "compatibilizer"; in the elastomer unit, the ratio of the flexible segment to the rigid segment (i.e. b:a) is any value between the ratio range of 30:1 and 1:5, preferably, the b / a ratio is 6:1.

[0016] In the structural formula 1, the rigid unit in the elastomer segment is a polystyrene polymer, including but not limited to: polystyrene, poly-p-methylstyrene; preferably, R1-R5 are each independently selected from hydrogen, halogen atoms, substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio side chains; more preferably, styrene without side chains (i.e., R1-R5 are all hydrogen) is selected as the rigid unit for reaction;

[0017] In the structural formula 1, the flexible unit in the elastomer segment is an isoprene polymer, including but not limited to: polyisoprene, poly-1,3-butadiene; preferably, R6-R7 are each independently selected from hydrogen, halogen atoms, substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio side chains; more preferably, isoprene without side chains (i.e., R6 is hydrogen, R7 is methyl) is selected as the flexible unit for reaction;

[0018] In the structural formula 1, the elastomer segment and the semiconductor segment are connected by a non-conjugated alkyl chain portion, preferably, c is an integer of 1-20;

[0019] In the structural formula 2, any monomer structure and any structural unit with similar functions developed on the basis of the monomer structure can be used for the A1 and A2 monomers in the formula 1:

[0020]

[0021] Preferably, R in any monomer in Formula 2 is independently selected from any one of the following: hydrogen, halogen atom, substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio side chain; More preferably, R is selected from any one of the following: substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio; Further preferably, R is selected from any one of the following: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, n-hexyl, n-heptyl, n-octyl, isooctyl, n-nonyl phenyl, fluorophenyl, bromophenyl, chlorophenyl, o-tolyl, p-tolyl, m-tolyl, o-ethylphenyl, p-ethylphenyl, m-ethylphenyl, o-isopropylphenyl, p-isopropylphenyl, m-isopropylphenyl, 1-naphthyl, 2-naphthyl, methylthio, ethylthio, propylthio, butylthio, pentylthio, hexylthio, heptylthio, octylthio, nonylthio, decylthio, methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, nonyloxy, decyloxy and the like.

[0022] According to an embodiment of the present invention, the structural formula of the compatibilizer represented by Formula 1 can be any of the following structures:

[0023]

[0024] The present invention optimizes and designs different feed ratios of semiconductor segments (conjugated polymers) and elastomer segments (including flexible units and rigid units) to ultimately synthesize a target polymer "compatibilizer".

[0025] In a second aspect, the present invention provides a method for preparing a polymer "compatibilizer" comprising a semiconductor segment and an elastomer segment as shown in the above formula 1.

[0026] The method for preparing the polymer "compatibilizer" comprising a semiconductor segment and an elastomer segment as shown in Formula 1 provided by the present invention comprises the following steps:

[0027] S1, polymerizing monomer A1 and monomer A2 through a coupling reaction to synthesize a semiconductor polymer;

[0028] S2, capping the semiconductor polymer obtained in step S1 through a coupling reaction (Stille reaction or Suzuki reaction);

[0029] S3, obtaining an elastomer segment through anionic polymerization;

[0030] S4, further polymerizing the end-capped semiconductor polymer obtained in step S2 and the elastomer fragment obtained in step S3 to finally obtain the target product "compatibilizer";

[0031] Wherein, the monomers A1 and A2 used in S1 are specifically any monomer structure shown in Formula 2 and structural units with similar functions developed on the basis of this monomer structure;

[0032] Preferably, the A1 part is a thiophene vinyl thiophene donor unit, the structural formula is

[0033] The A2 portion is a diketopyrrolopyrrole receptor unit, and the structural formula is wherein the R group is 2-decyltetradecyl; the end-capping group in S2 is a thiophene group or a phenyl group or a dithiophene group,

[0034] The thiophene group is Preferably, R8 and R9 are each independently selected from hydrogen, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, an alkoxy group or an alkylthio side chain;

[0035] The dithiophene group is Preferably, R 10 , R 11 Each is independently selected from hydrogen, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, an alkoxy group or an alkylthio side chain.

[0036] In S3, the elastomer segment is polymerized from a flexible unit and a rigid unit; in the elastomer unit, the ratio of the flexible segment to the rigid segment (i.e., b:a) is in the range of 30:1 to 1:5, preferably, the ratio of b / a is 6:1;

[0037] Wherein, the rigid unit in the elastomer segment is a polystyrene polymer, including but not limited to: polystyrene, poly-p-methylstyrene; preferably, R1-R5 are each independently selected from hydrogen, halogen atoms, substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio side chains; preferably, styrene without side chains is selected as the rigid unit for reaction;

[0038] The flexible unit in the elastomer segment is an isoprene polymer, including but not limited to: polyisoprene, poly-1,3-butadiene; preferably, R6-R7 are each independently selected from hydrogen, halogen atoms, substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio side chains; preferably, isoprene without side chains is selected as the flexible unit for reaction;

[0039] The product obtained in S4 conforms to the structure of the "compatibilizer" in Formula 1.

[0040] The reaction route of the preferred embodiment of the above preparation method can be expressed as reaction route (A):

[0041] Taking the preparation of "compatibilizer" PDVT-SI as an example, the synthetic route (A) is as follows:

[0042]

[0043] The preparation method of the above-mentioned "compatibilizer", the specific reaction steps (Stille reaction) include:

[0044] (a1) weighing a certain amount of brominated monomer and tin compound monomer, catalyst and ligand in an inert atmosphere, and then adding a reaction solvent to mix, to obtain a mixed reaction liquid; performing a Freeze-Pump-Thaw operation (freeze-vacuum-thaw three-step cycle) three times in liquid nitrogen under anhydrous and oxygen-free conditions to remove water and oxygen in the solvent of the reaction bottle;

[0045] (a2) heating and stirring the mixed solution under anhydrous and oxygen-free conditions to react;

[0046] (a3) After the reaction is completed, the mixture is cooled to room temperature, a methanol solution containing a small amount of hydrochloric acid is added to quench the reaction, and then Soxhlet extraction is performed with methanol, acetone and n-hexane in sequence, and then the precipitated polymer is obtained by filtering (or suction filtration); pure chlorobenzene (or chloroform) is added again to extract the polymer with a Soxhlet extractor to obtain a conjugated polymer as a semiconductor fragment (i.e., product c in reaction route (A));

[0047] (a4) weighing appropriate amounts of the end-capping compound, the conjugated polymer obtained in step (3), a catalyst and a ligand, and subjecting the conjugated polymer obtained in step (a3) ​​to an end-capping reaction (Stille reaction) in an inert atmosphere;

[0048] (a5) subjecting the reaction system obtained after the reaction to Soxhlet extraction in methanol, acetone and n-hexane in turn, and then filtering (or suction filtration) to obtain a precipitated polymer; re-adding chlorobenzene (or trichloroethane) to extract the polymer through a Soxhlet extractor to obtain a capped conjugated polymer (i.e., product d in reaction route (A));

[0049] (a6) adding a certain amount of anhydrous toluene, anhydrous tetrahydrofuran, and anhydrous styrene in an inert atmosphere, and then adding a certain amount of 0.1 M initiator n-butyl lithium to obtain a red reaction solution, and heating the reaction at 40-60° C. for 0.5 to 2 hours;

[0050] (a7) adding anhydrous isoprene dropwise to the reaction solution in step (a6), the reaction solution turns slightly yellow, and heating the reaction solution at 40-60° C. for 1 to 3 hours to obtain a reaction system containing an elastomer segment polymer (i.e., product e in reaction route (A));

[0051] (a8) in anhydrous and oxygen-free atmosphere, after completely dissolving the capped conjugated polymer obtained in step (a5) in toluene, adding the polymer to the reaction system containing the elastomer segment in step (a7) according to the designed feed ratio, and heating the reaction at 50-100° C. for 1 to 12 hours;

[0052] (a9) After the reaction is completed, the mixture is cooled to room temperature, a small amount of methanol is added to quench the mixture, and the mixture is stirred for 10-90 minutes. An appropriate amount of dilute hydrochloric acid is then added, and the mixture is extracted with dichloromethane and deionized water for at least three times. The crude product is obtained after being spin-dried.

[0053] Furthermore, the method also includes the step of separating and purifying the obtained crude product, which is specifically as follows:

[0054] (a10) separating and purifying the crude product by column chromatography. Non-polar polystyrene-isoprene can be eluted by column chromatography to separate the target product.

[0055] (a11) The target product mixed with silica gel is taken out, washed with tetrahydrofuran, filtered to remove the silica gel, and then the obtained mixed solution is spin-dried to obtain a pure polymer "compatibilizer".

[0056] Further, in the step (a1), the brominated monomer is selected from: 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione; the tin-substituted monomer is selected from: (E)-1,2-bis(5-(trimethyltinyl)thiophene-2-yl)ethylene;

[0057] The molar ratio of the brominated monomer to the tin-substituted monomer may be 1:1-1:1.05 (the brominated monomer is slightly less than the tin-substituted monomer), and the final molecular weight of the conjugated polymer can be adjusted by the molar ratio of the two;

[0058] The catalyst can be one of tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetonepalladium)Pd(dba)2. Preferably, the catalyst tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3] is selected. The amount of the catalyst is 1-5% of the molar amount of the tin-substituted monomer in the reaction system. Too much catalyst is not conducive to the improvement of the molecular weight.

[0059] The ligand may be tri(o-methylphenyl)phosphine P-(o-tol)3; one of triphenylphosphine PPh3 and tri-tert-butylphosphine P(t-Bu)3. Preferably, the ligand tri(o-methylphenyl)phosphine P-(o-tol)3 is selected, and the molar ratio of the amount of the ligand to the amount of the catalyst is 2:1-10:1.

[0060] The reaction solvent may be one of solvents such as chlorobenzene, toluene, xylene, dichlorobenzene, trimethylbenzene, trichlorobenzene, chloronaphthalene, chlorotoluene, chloroxylene, and chloroethylbenzene. Preferably, chlorobenzene is selected as the reaction solvent.

[0061] Furthermore, in the step (a2), the reaction temperature is 115-130° C., and the reaction time is 48-72 hours.

[0062] Furthermore, in the step (a3), the quenching reaction is stirred for 1-3 hours, and Soxhlet extraction is performed with methanol, acetone and n-hexane in sequence for 12-24 hours.

[0063] Furthermore, if the conjugated polymer as the semiconductor fragment obtained in step (a3) ​​is commercially available, it can also be directly used as a raw material to start the preparation from step (a4).

[0064] Furthermore, in the step (a4), the added end-capping compound has the structural formula The molar ratio of the end-capping compound to the conjugated polymer is 1:1-1:1.05;

[0065] In the step (a4), the catalyst is one of tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetonepalladium)Pd(dba)2. Preferably, the catalyst tetrakis(triphenylphosphine)palladium Pd(PPh3)4 is selected. The amount of the catalyst is 1-5% of the molar amount of the end-capping compound in the reaction system. Too much catalyst is not conducive to the increase of molecular weight.

[0066] In the step (a4), the ligand may be tri(o-methylphenyl)phosphine P-(o-tol)3; one of triphenylphosphine PPh3 and tri-tert-butylphosphine P(t-Bu)3. Preferably, the ligand tri(o-methylphenyl)phosphine P-(o-tol)3 is selected, and the molar ratio of the amount of the ligand to the amount of the catalyst is 2:1-10:1.

[0067] In the step (a4), the reaction is carried out in a reaction solvent, and the reaction solvent can be one of solvents such as chlorobenzene, toluene, xylene, dichlorobenzene, trimethylbenzene, trichlorobenzene, chloronaphthalene, chlorotoluene, chloroxylene, chloroethylbenzene, etc. Preferably, chlorobenzene is selected as the reaction solvent;

[0068] The reaction conditions of the end-capping reaction are heating the reaction at a temperature range of 100°C to 130°C for 10-60 hours; preferably, the reaction is carried out at 125°C for 24 hours;

[0069] Furthermore, in the step (a5), the extraction time is 12-24 hours.

[0070] Furthermore, in step (a6), the amount of anhydrous tetrahydrofuran added is 0.5-20 times the molar amount of n-butyl lithium, and the amount of anhydrous toluene added is 5-20 times the molar amount of anhydrous styrene; and the amount of n-butyl lithium added is 1 / 200 of the molar amount of styrene.

[0071] Furthermore, in the step (a6), preferably, the reaction is heated at 50° C. for 1 hour.

[0072] Furthermore, in the step (a7), the molar amount of the added isoprene needs to be regulated according to the molar amount of styrene in the reaction solution of step (s6), and the feeding molar ratio of isoprene to styrene is 1:1-1:100, preferably, the feeding molar ratio is 1:5-1:10.

[0073] Furthermore, in the step (a7), preferably, the reaction is heated at 50° C. for 2 hours.

[0074] Furthermore, in the step (a8), the molar amount of the end-capped conjugated polymer does not exceed 50% of the total molar amount of the end-capped conjugated polymer and the elastomer segment-containing polymer, otherwise the obtained product is not a "compatibilizer".

[0075] Furthermore, in the step (a8), preferably, the reaction is carried out at 75° C. for 6 hours;

[0076] Furthermore, a small amount of methanol is added in step (a9) to quench the reaction, and an appropriate amount of dilute hydrochloric acid is added to neutralize the alkaline by-products produced during the reaction.

[0077] Furthermore, in step (a10), the eluent used in the column chromatography is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to a mixed solvent of petroleum ether and dichloromethane (petroleum ether: dichloromethane = 1:1, v / v).

[0078] Furthermore, in step (a11), the silica gel mixture is washed with tetrahydrofuran three times. Ultrasonic treatment is prohibited during this process, and the silica gel must be completely removed during the filtration process.

[0079] The reaction route of the preferred embodiment of the above preparation method can also be expressed as reaction route (B):

[0080] Taking the preparation of "compatibilizer" PDVT-SI as an example, the synthetic route (B) is as follows:

[0081]

[0082] The preparation method of the above-mentioned "compatibilizer" includes the following specific reaction (Suzuki reaction) steps:

[0083] (b1) weighing a certain amount of brominated monomer and borate end-capping compound, catalyst and base in an inert atmosphere, and then adding a reaction solvent to mix to obtain a mixed reaction solution, and performing a Freeze-Pump-Thaw operation (freeze-vacuum-thaw three-step cycle) three times in liquid nitrogen under anhydrous and oxygen-free conditions to remove oxygen in the solvent of the reaction bottle;

[0084] (b2) heating and stirring the mixed solution under an inert gas atmosphere to react;

[0085] (b3) After the reaction is completed, the mixture is cooled to room temperature, and then Soxhlet extraction is performed with methanol, acetone and n-hexane in sequence, and then the precipitated polymer is obtained by filtering (or suction filtration); pure chlorobenzene (or chloroform) is added again to extract the polymer with a Soxhlet extractor to obtain a conjugated polymer as a semiconductor fragment (i.e., product c in reaction route (B));

[0086] (b4) weighing appropriate amounts of the end-capping compound, the conjugated polymer obtained in step (3), a catalyst and a base, and subjecting the target conjugated polymer obtained in step (b3) to an end-capping reaction (Suzuki reaction) in an inert atmosphere;

[0087] (b5) extracting the reaction system obtained after the reaction in methanol, acetone and n-hexane in turn, and then filtering (or suction filtration) to obtain a crude polymer after end-capping; re-adding chlorobenzene (or trichloroethane) to extract the polymer through a Soxhlet extractor to obtain an end-capped conjugated polymer (i.e., product d in reaction route (B));

[0088] (b6) adding a certain amount of anhydrous toluene, anhydrous tetrahydrofuran, and anhydrous styrene in an inert atmosphere, and then adding a certain amount of 0.1 M initiator n-butyl lithium to obtain a red reaction solution, and heating the reaction at 40-60° C. for 0.5 to 2 hours;

[0089] (b7) adding anhydrous isoprene dropwise to the reaction solution in step (b6), the reaction solution turns slightly yellow, and heating the reaction solution at 40-60° C. for 1 to 3 hours to obtain a reaction system containing an elastomer segment polymer;

[0090] (b8) in anhydrous and oxygen-free atmosphere, after completely dissolving the capped conjugated polymer obtained in step (b5) in toluene, adding the end-capped conjugated polymer obtained in step (b5) into the reaction system containing the elastomer segment polymer in step (b7) according to the designed feed ratio, and heating the reaction at 50-100° C. for 1 to 12 hours;

[0091] (b9) After the reaction is completed, the mixture is cooled to room temperature, a small amount of methanol is added to quench the mixture, and the mixture is stirred for 10-90 minutes. An appropriate amount of dilute hydrochloric acid is then added, and the mixture is extracted with dichloromethane and deionized water for at least three times. The crude product is obtained after being spin-dried.

[0092] Furthermore, the method also includes the step of separating and purifying the obtained crude product, which is specifically as follows:

[0093] (b10) separating and purifying the crude product by column chromatography, wherein the non-polar polystyrene-isoprene can be eluted by column chromatography, thereby separating the target product;

[0094] (b11) The target product mixed with silica gel is taken out, washed with tetrahydrofuran, filtered to remove the silica gel, and then the obtained mixed solution is spin-dried to obtain a pure polymer "compatibilizer".

[0095] Further, in the step (b1), the brominated monomer is selected from: 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione; the borate ester monomer is selected from: (E)-1,2-bis(5-(4,4,5,5-tetramethyl)-1,3,2-dioxaborolane-2-yl)thiophenevinylthiophene;

[0096] The molar ratio of the brominated monomer to the borate monomer is 1:1-1:1.05 (the brominated monomer is slightly less than the borate monomer), and the final molecular weight of the conjugated polymer can be adjusted by the molar ratio of the two;

[0097] The catalyst is one of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride PdCl2(dppf), tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetone palladium Pd(dba)2. Preferably, the catalyst tetrakis(triphenylphosphine)palladium Pd(PPh3)4 is selected. The amount of the catalyst is 1-5% of the molar amount of the borate end-capping compound in the reaction system. Too much catalyst is not conducive to the increase of molecular weight.

[0098] The base can be one of lithium carbonate, potassium carbonate, sodium carbonate, cesium carbonate, potassium acetate, tetrabutylammonium fluoride, cesium fluoride, potassium fluoride, and potassium phosphate. Preferably, potassium carbonate is selected;

[0099] The reaction solvent may be a toluene and water mixed system, a toluene and tetrahydrofuran mixed system, dioxane, N,N-dimethylformamide and the like solvent system. Preferably, a toluene and water mixed system is selected as the reaction solvent;

[0100] Furthermore, in the step (b2), the reaction temperature is 80-130° C., and the reaction time is 24-72 hours.

[0101] Furthermore, in the step (b3), the reaction is quenched and stirred for 1-3 hours, and Soxhlet extraction is performed with methanol, acetone, and n-hexane in sequence for 12-24 hours.

[0102] Furthermore, if the conjugated polymer as the semiconductor fragment obtained in step (b3) is commercially available, it can also be directly used as a raw material to start the preparation from step (b4).

[0103] Furthermore, in the step (b4), the added end-capping compound has the structural formula The molar ratio of the end-capping compound to the conjugated polymer is 1:1-1:1.05;

[0104] In the step (b4), the catalyst is tetrakis(triphenylphosphine)palladium Pd(PPh3)4, and the amount of the catalyst is 1-5% of the molar amount of the borate-terminated compound in the reaction system. Too much catalyst is not conducive to the increase of molecular weight;

[0105] In the step (b4), the base may be one of lithium carbonate, potassium carbonate, sodium carbonate, cesium carbonate, potassium acetate, tetrabutylammonium fluoride, cesium fluoride, potassium fluoride, and potassium phosphate, preferably potassium carbonate;

[0106] In the step (b4), the reaction is carried out in a reaction solvent, and the reaction solvent may be one of a solvent system such as a toluene and water mixture system, a toluene and tetrahydrofuran mixture system, dioxane, N,N-dimethylformamide, etc. Preferably, a toluene and water mixture system is selected as the reaction solvent;

[0107] In the step (b4), the end-capping reaction is carried out under the conditions of heating at a temperature range of 80° C. to 130° C. for 10-60 hours; preferably, at 100° C. for 48 hours.

[0108] Furthermore, in the step (b5), the extraction time is 12-24 hours.

[0109] Furthermore, in the step (b6), the amount of anhydrous tetrahydrofuran added is 0.5-20 times the molar amount of n-butyl lithium, the amount of anhydrous toluene added is 5-20 times the molar amount of anhydrous styrene; the amount of n-butyl lithium added is 1 / 200 of the molar amount of styrene;

[0110] Furthermore, in the step (b6), preferably, the reaction is heated at 50° C. for 1 hour.

[0111] Furthermore, in the step (b7), the molar amount of the added isoprene needs to be regulated according to the molar amount of styrene, and the feed molar ratio of isoprene to styrene is 1:1-1:100, preferably, the feed molar ratio is 1:5-1:10.

[0112] Furthermore, the molar amount of the end-capped conjugated polymer in step (b8) does not exceed 50% of the total molar amount of the end-capped conjugated polymer and the elastomer segment-containing polymer, otherwise the obtained product is not a "compatibilizer".

[0113] Furthermore, a small amount of methanol is added in step (b9) to quench the reaction, and an appropriate amount of dilute hydrochloric acid is added to neutralize the alkaline by-products produced during the reaction.

[0114] Furthermore, in step (b10), the eluent used in the column chromatography is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to a mixed solvent of petroleum ether and dichloromethane (petroleum ether: dichloromethane = 1:1, v / v).

[0115] Furthermore, in step (b11), the silica gel mixture is washed with tetrahydrofuran for 3 times. Ultrasonic treatment is prohibited during this process, and the silica gel must be completely removed during the filtration process.

[0116] The present invention provides a method for preparing the polymer "compatibilizer" based on semiconductor polymer and elastomeric fragments, wherein the "compatibilizer" can effectively connect the conjugated polymer and the elastomeric polymer through the principle of similar dissolving.

[0117] The present invention also provides the application of the polymer "compatibilizer" based on the semiconducting polymer and the elastomeric segment.

[0118] The polymer "compatibilizer" based on semiconductor segments and elastomer segments provided by the present invention is used to prepare a composite active layer with both efficient charge transport and excellent stretchability, and to construct a flexible and stretchable field effect transistor.

[0119] The present invention also protects a flexible and stretchable field effect transistor.

[0120] The present invention protects a flexible and stretchable field effect transistor, whose active layer includes a polymer "compatibilizer" based on semiconductor segments and elastomer segments provided by the present invention.

[0121] Furthermore, the active layer also includes a polymer semiconductor and an elastomer.

[0122] Furthermore, the amount of the compatibilizer added is 0.01%-40% of the total mass of the polymer semiconductor and the elastomer, preferably 1%-5%.

[0123] The present invention further provides a method for preparing the above-mentioned flexible and stretchable field effect transistor.

[0124] The method for preparing a flexible and stretchable field effect transistor provided by the present invention comprises the following steps:

[0125] (a) firstly, adding the "compatibilizer" provided by the present invention to a mixed solution of a polymer semiconductor and an elastomer in a certain proportion, and preparing a blended semiconductor film on a substrate by spin coating;

[0126] (b) preparing an elastic substrate for transferring the blended semiconductor film;

[0127] (c) Using an elastic substrate, the blended semiconductor film is transferred and stretched with different forces, and then transferred to a target substrate again, source and drain electrodes are evaporated to obtain the flexible and stretchable field effect transistor, and the film performance under different stresses is tested.

[0128] Furthermore, in step (a), the polymer semiconductor and the elastomer are dissolved in chlorobenzene and heated to dissolve them to obtain a mixed solution;

[0129] Furthermore, in step (a), the polymer semiconductor may be selected from at least one of the following: PDVT-10 molecule, PDPPTT; and the elastomer may be selected from: SEBS.

[0130] The mass ratio of the polymer semiconductor to the elastomer may be 1:(1-100), preferably 1:1.

[0131] The amount of the compatibilizer added is 0.01%-40% of the total mass of the polymer semiconductor and the elastomer, preferably 1%-5%.

[0132] According to an embodiment of the present invention, further, in step (a), the polymer semiconductor is PDVT-10 and the elastomer is SEBS. PDVT-10 and SEBS are physically blended in a certain ratio, and the mass ratios (PDVT-10: SEBS) are 1:0, 3:1, 1:1, 3:7, and 1:9, respectively. Preferably, on the basis of a blending ratio of 1:1 between PDVT-10 and SEBS, a compatibilizer (such as PDVT-SI) is added, and the mass of the added compatibilizer is 0.1%-10% of the total mass of the PDVT-10 semiconductor polymer and the SEBS elastomer, specifically 0.1%, 1%, 3%, 5%, and 10%.

[0133]

[0134] Further, in step (a), when the mass ratio of PDVT-10 to SEBS is 1:0, the set spin coating rate is 1500rpm, and the spin coating speed of the other four ratios (the mass ratio of PDVT-10 to SEBS is 3:1, 1:1, 3:7, 1:9) is 4000rpm. The selected substrate is an OTS-modified silicon wafer. The evaporated metal is gold, which serves as the source and drain electrodes. The electrical properties tested show that the more preferred mass ratio of PDVT-10, SEBS, and compatibilizer is 50:50:3.

[0135] Furthermore, in step (c), the elastic substrate is PDMS, and its preparation includes mixing the PDMS precursor and Dow Corning SYLGARD 184 curing agent at a mass ratio of 12:1, pouring into a glass culture dish, curing at 80° C. for 12 hours, and cutting into strips for later use.

[0136] Furthermore, in step (d), a PDMS substrate is attached to the film prepared by spin coating, quickly peeled off, and then placed on a stretching device, stretched with different forces including 0%, 25%, 50%, 75%, and 100%, and then transferred to an unmodified silicon wafer (i.e., the target substrate), and finally gold electrodes are evaporated as source and drain electrodes to test the performance.

[0137] After preparation, the film properties under different stresses were also tested: the film was cyclically stretched on a stretching apparatus and the electrical properties under cyclic stress were tested.

[0138] Furthermore, the number of cyclic stretching includes 1 time, 10 times, 100 times, 500 times, and 1000 times.

[0139] Compared with the prior art, the present invention has the following beneficial technical effects:

[0140] The present invention prepares polymer "compatibilizers" based on semiconductor polymers and elastomer segments, selects different types of conjugated polymers and different elastomeric polymer soft segment structures, and prepares different types of polymer "compatibilizers". One of the "compatibilizers" with the best mechanical properties is selected and blended with different types of conjugated polymers and elastomers to obtain a blended composite semiconductor film with excellent mechanical and electrical properties. The electrical properties of the blended film remain stable and higher than the initial performance after 1000 cycles of stretching under a fixed 100% strain, providing new ideas for subsequent research on stretchable semiconductor systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0141] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0142] Figure 1 It is a physical blending method of the conjugated polymer, the "compatibilizer" and the elastomer in the embodiment of the present invention;

[0143] Figure 2 The infrared spectra of SEBS, polymer PDVT-10 and compatibilizer PDVT-SI in Example 1 of the present invention;

[0144] Figure 3 is the ultraviolet absorption spectrum of the “compatibilizer” in Example 1 of the present invention;

[0145] Figure 4 The "compatibilizer" prepared in Example 1 of the present invention, the semiconductor conjugated polymer PDVT-10 and the elastomer SEBS are blended, and the transfer curve (left) and mobility change curve (right) of the composite blend film of the compatibilizer at different mass ratios (0%, 0.1%, 1%, 3%, 5%, 10%);

[0146] Figure 5 This is an optical microscope image of a composite blend film of a semiconductor conjugated polymer PDVT-10 and an elastomer SEBS with a blend ratio of 50:50 (mass ratio) prepared in Comparative Example 1 of the present invention under different stretching conditions (0%, 25%, 50%, 75%, 100%, 125%, 150%), and cracks appeared under 100% strain;

[0147] Figure 6This is an optical microscope image of a composite blend film of the "compatibilizer", semiconductor conjugated polymer and elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) prepared in Example 1 of the present invention under different stretching conditions (0%, 25%, 50%, 75%, 100%, 125%, 150%), and cracks appeared under 150% stretching;

[0148] Figure 7 The transfer curves of the composite blend film of the "compatibilizer", semiconductor conjugated polymer PDVT-10 and elastomer SEBS with a blend ratio of 3:50:50 (mass ratio) prepared in Example 1 of the present invention parallel to the stretching direction (left) and perpendicular to the stretching direction (middle) under different strains, and the corresponding mobility change trend curve under stretching (right);

[0149] Figure 8 The mobility change trend curves of the composite blend films prepared in Example 1 (W / ) of the present invention and Comparative Example 1 (W / O) under different strains parallel ( / / ) and perpendicular (⊥) to the stretching direction;

[0150] Fig. 9 The output curve (left) and the transistor device mobility distribution diagram (right) of the composite blend film of the "compatibilizer", the semiconductor conjugated polymer PDVT-10 and the elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) prepared in Example 1 of the present invention;

[0151] Fig.10 Typical transfer curves of the composite blend films of the "compatibilizer", semiconductor conjugated polymer PDVT-10 and elastomer SEBS in different blending ratios of 3:50:50 (left) prepared in Example 1 of the present invention and the semiconductor conjugated polymer PDVT-10 and elastomer SEBS in different blending ratios of 50:50 (right) prepared in Comparative Example 1 under different stretching conditions.

[0152] Fig.11 These are the change trend curves of mobility, on-state current and off-state current of the composite blend film of the "compatibilizer" prepared in Example 1 of the present invention, the semiconductor conjugated polymer PDVT-10 and the elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) under different stretching directions parallel to (left) and perpendicular to (right) the stretching direction.

[0153] Fig.12These are the mobility change trend curves of the composite blend film (W / ) of the "compatibilizer", the semiconductor conjugated polymer PDVT-10 and the elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) prepared in Example 1 of the present invention, and the composite blend film (W / O) of the semiconductor PDVT-10 and the elastomer SEBS in a blending ratio of 50:50 (mass ratio) in Comparative Example 1 under 50% stretching and after stretching release, perpendicular (left) and parallel (right) to the stretching direction.

[0154] Fig.13 The mobility change curve of the composite blend film of the "compatibilizer" prepared in Example 2 of the present invention, the semiconductor conjugated polymer PDPPTT and the elastomer SEBS, and the compatibilizer at different mass ratios (0%, 0.1%, 1%, 3%, 5%, 10%);

[0155] Fig.14 The composite blend film (W / ) of the "compatibilizer", the semiconductor conjugated polymer PDPPTT and the elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) prepared in Example 2 of the present invention, and the composite blend film (W / O) of the semiconductor PDPPTT and the elastomer SEBS in a blending ratio of 50:50 (mass ratio) in Comparative Example 2 are the change trend curves of the corresponding mobility in parallel and perpendicular stretching directions under different strains;

[0156] Fig.15 The mobility change curve of the composite blend film of the "compatibilizer" prepared in Example 3 of the present invention, the semiconductor conjugated polymer N2200 and the elastomer SEBS is shown in FIG. 1 , and the mobility change curve of the composite blend film of the compatibilizer at different mass ratios (0%, 0.1%, 1%, 3%, 5%, 10%) is shown in FIG.

[0157] Fig.16 The graphs show the mobility change trend curves of the composite blend film (W / ) of the "compatibilizer", semiconductor conjugated polymer N2200 and elastomer SEBS in a blending ratio of 3:50:50 (mass ratio) prepared in Example 3 of the present invention, and the composite blend film (W / O) of semiconductor N2200 and elastomer SEBS in a blending ratio of 50:50 (mass ratio) in Comparative Example 3 under different strains in parallel and perpendicular stretching directions. DETAILED DESCRIPTION

[0158] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0159] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0160] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0161] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0162] The words “include,” “comprises,” “has,” “contains,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0163] The physical blending method of all embodiments of the present invention is as follows Figure 1 shown.

[0164] The anhydrous toluene, anhydrous tetrahydrofuran, and anhydrous n-hexane in the embodiments of the present invention refer to anhydrous and oxygen-free organic solvents treated by a solvent treatment system, and the solvents are added in a glove box during the experimental operation process to strictly ensure that the experiment is carried out under anhydrous and oxygen-free conditions.

[0165] The anhydrous styrene in the embodiment of the present invention refers to adding an appropriate amount of calcium hydride to styrene under anhydrous and oxygen-free conditions, stirring in the dark for 7 days, and then distilling out a transparent and clear solvent at 45°C-50°C by reduced pressure distillation as anhydrous and oxygen-free styrene for the next experimental operation. The experimental operation process is carried out in a glove box to strictly ensure that the experiment is carried out under anhydrous and oxygen-free conditions.

[0166] The anhydrous isoprene in the embodiment of the present invention refers to adding an appropriate amount of calcium hydride to isoprene under anhydrous and oxygen-free conditions, stirring in the dark for 7 days, and then distilling out a transparent and clear solvent at 45°C-50°C by reduced pressure distillation as anhydrous and oxygen-free styrene for the next experimental operation. The experimental operation process is carried out in a glove box to strictly ensure that the experiment is carried out under anhydrous and oxygen-free conditions.

[0167] Silicon wafer modification in the embodiment of the present invention: first use deionized water to ultrasonically treat for 10 minutes (to remove water-soluble impurities on the surface of the silicon wafer), add about 15mL of hydrogen peroxide and 35mL of concentrated sulfuric acid respectively, heat and boil for about 15 minutes, then use deionized water to ultrasonically treat for 10 minutes, and isopropanol to ultrasonically treat for 10 minutes. The cleaned silicon wafer is placed in a vacuum drying oven and heated to 90°C for 30 minutes to remove residual water molecules on the surface of the silicon wafer. Then a small amount of n-octadecyltrichlorosilane (OTS) is added dropwise to the center of the culture dish, heated to 120°C, and cooled to room temperature after 2 hours. The modification is completed. The modified silicon wafer is ultrasonically treated with chloroform, n-hexane and isopropanol for 10 minutes each to remove the multi-layered OTS on the surface of the silicon wafer to ensure that the OTS is a single-layer modification, and finally quickly blown dry with nitrogen.

[0168] In the embodiment of the present invention, the semiconductor film is prepared by spin coating in a nitrogen atmosphere in a glove box. The coating machine is rotated at 500 rpm for 5 seconds and then at 4000 rpm for 60 seconds to prepare the semiconductor film. After the preparation is completed, it is placed on a hot stage at 150°C for annealing for 30 minutes to further improve the stacking and increase the mobility.

[0169] In the embodiment of the present invention, a metal mask is attached to part of the thin film, 20 nm Au is evaporated as source and drain electrodes, and then the field effect performance is characterized by an electrical test system.

[0170] In the embodiment of the present invention, the PDMS precursor (prepolymer) and the Dow Corning SYLGARD 184 curing agent are mixed evenly at a mass ratio of 12:1, poured into a flat culture dish, cured at 80° C. for 12 hours, and after complete curing, cut into long strips for use as a flexible transfer substrate.

[0171] In the embodiment of the present invention, PDMS is adhered to the surface of the semiconductor film, quickly peeled off, stretched by 0%, 25%, 50%, 75%, and 100%, and then transferred to the surface of an unmodified silicon wafer.

[0172] In the embodiment of the present invention, PDMS is adhered to the surface of the semiconductor film, quickly peeled off, stretched under 100% stress, and cyclically stretched 10 times, 100 times, 500 times, and 1000 times, affixed with a metal mask, evaporated source and drain electrodes, and tested for electrical properties.

[0173] Example 1

[0174] In this embodiment, based on the "compatibilizer" PDVT-SI, the blended polymer semiconductor is PDVT-10, and the blended elastomeric polymer is SEBS, and the structure is as follows:

[0175]

[0176] The polymer semiconductor used (which is also the conjugated polymer of the semiconductor segment in PDVT-SI) PDVT-10 has a molecular weight of 49 kDa / mol; the SEBS used is H1221 (Asahi Kasei).

[0177] The blended film based on "compatibilizer" PDVT-SI, polymer semiconductor PDVT-10 and SEBS was prepared by the following method:

[0178] 1. Preparation of "Compatibilizer" PDVT-SI

[0179] 1) The target polymer was capped in an inert atmosphere, and appropriate amounts of the capping compound 5-(3-bromopropyl)thiophen-2-yl)trimethyltin (2.70 mg), polymer PDVT-10 (200 mg), catalyst tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3] (0.4 mg) and ligand tris(o-methylphenyl)phosphine P-(o-tol)3 (1.2 mg) and 3 ml of ultra-dry chlorobenzene were weighed in a 10 ml Schlenk reaction tube and reacted at 125° C. for 24 hours;

[0180] 2) The polymer after the reaction is precipitated in methanol, filtered, extracted, dried, and weighed to obtain a capped conjugated polymer PDVT-TP; the structural formula is shown below:

[0181]

[0182] 3) Add 20 ml of anhydrous toluene, 40 ul of anhydrous tetrahydrofuran, 1.85 ml of anhydrous styrene, and then add 0.08 mol of 0.1 M initiator n-butyl lithium in an inert atmosphere to obtain a red reaction solution, and react at 50° C. for 1 hour;

[0183] 4) adding anhydrous isoprene (9.6 ml, 96 mmol) dropwise to the reaction solution in step 3), and reacting at 50° C. for 2 hours to obtain a reaction solution containing an elastomer segment polymer;

[0184] 5) In anhydrous and oxygen-free atmosphere, the blocked conjugated polymer PDVT-TP (40 mg) was completely dissolved in 50 ml of anhydrous toluene, and then 12 ml of the reaction solution in step 4) was quickly added to the toluene solution containing PDVT-TP according to the designed ratio, and the reaction was carried out at 75° C. for 6 hours;

[0185] 6) After the reaction is completed, cool to room temperature, add 2 ml of methanol to the reaction bottle and stir for 30 minutes, then add 2 ml of dilute hydrochloric acid, and extract three times with dichloromethane and deionized water, and spin dry to obtain a crude product;

[0186] 7) Separating and purifying the crude product by column chromatography, the non-polar polystyrene-isoprene can be eluted by column chromatography, the eluent is a mixed solvent of petroleum ether and dichloromethane, the polarity gradually increases from pure petroleum ether to petroleum ether: dichloromethane = 1:1, v / v, so that the target product block copolymer "compatibilizer" is separated;

[0187] 8) The target product mixed with silica gel was taken out, washed with tetrahydrofuran, filtered to remove the silica gel, and then the obtained mixed solution was spin-dried to obtain a pure block copolymer "compatibilizer", namely PDVT-SI, which was tested by GPC at room temperature THF phase: M n Molecular weight = 95.9 kDa, M w Molecular weight = 114.9 kDa, PDI = 1.20. In the compatibilizer PDVT-SI, n is 41, a is 95, and b is 570. 1 H NMR (400MHz): δ (ppm) 8.55 (s, 2H), 7.12-7.09 (m, 6H), 6.62-6.54 (m, 4H), 5.55 (d, 2H), 5.09 (dq ,6H),4.70(dd,4H),3.93(d,4H),2.05-1.96(m,50H),1.58-1.07(m,52H),0.89-0.76(br,18H).

[0188] 2. Preparation of blended films

[0189] 9) Weigh 5mg PDVT-10 and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS, then prepare a 10mg / ml chlorobenzene solution of compatibilizer PDVT-SI, take different amounts of compatibilizer solution and add it to the above solution to prepare the final compatibilizer ratio (this ratio refers to the ratio of the mass of the compatibilizer to the total mass of the two parts of PDVT-10 semiconductor polymer and SEBS elastomer) of 0.1%, 1%, 3%, 5%, and 10%. In an atmospheric atmosphere, place the solution on a hot plate at 75°C and heat it for 1h, stirring continuously until it is completely dissolved. After the coater rotates at 500rpm on the OTS-modified silicon wafer for 5s, it rotates at 4000rpm for 60s to prepare a semiconductor film. After the preparation is completed, it is placed on a hot plate at 150°C for annealing for 30min to further improve the stacking and increase the mobility. Then evaporate gold as the source and drain electrodes to construct an organic field effect transistor.

[0190] 10) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat culture dish, cured at 80°C for 12 hours, and cut into long strips for use after complete curing. As a flexible transfer substrate, PDMS was used to adhere to the surface of the semiconductor film, quickly peeled off, stretched 0%, 25%, 50%, 75%, and 100%, and then transferred to the surface of the unmodified silicon wafer. PDMS was then used to adhere to the surface of the semiconductor film, quickly peeled off, stretched under 100% stress, and cyclically stretched 10 times, 100 times, 500 times, and 1000 times. Among them, the mechanical property curve is shown in the figure. Figure 4 The electrical properties are shown in Figure 5 , 6 , 7, 8, and 9. The results show that the blended film exhibits excellent electrical and mechanical properties when used as a semiconductor layer in transistor devices. In terms of electrical properties, the mobility of the transistor device prepared by the blended film remains unchanged in the vertical direction under different strains within the range of 100% strain, and the mobility does not decrease after the film is released, and there is a significant increase in the parallel direction under different strains within the range of 100% strain, and the mobility remains unchanged after the film is released. On the other hand, the electrical performance of the transistor device planted with the blended film is very stable and remains unchanged in the vertical and parallel stretching directions after 1000 cycles of stretching under 100% strain.

[0191] Comparative Example 1 (Comparative Example 1)

[0192] In order to more clearly demonstrate the improvement and optimization of the device performance by the "compatibilizer", Comparative Example 1 was compared and analyzed with Example 1, wherein no "compatibilizer" was added in Comparative Example 1, and all other aspects such as preparation and testing were the same as Example 1.

[0193] Based on the conjugated polymer PDVT-10, the elastomeric polymer is SEBS with the following structure:

[0194]

[0195] The conjugated polymer PDVT-10 used has a molecular weight of 74 kDa / mol; the SEBS used is H1221 (Asahi Kasei).

[0196] The blended film based on conjugated polymer PDVT-10 and SEBS was prepared by the following method:

[0197] 1. Preparation of blended films

[0198] 1) Weigh 5mg PDVT-10 and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS. In an atmospheric atmosphere, place the solution on a hot plate at 75°C for 1h and stir continuously until it is completely dissolved. The gelator rotates on the OTS-modified silicon wafer at 500rpm for 5s, and then rotates at 4000rpm for 60s to prepare a blended film. After preparation, place it on a hot plate at 150°C for annealing for 30min to further improve stacking and increase mobility. Then evaporate gold as the source and drain electrodes to construct an organic field-effect transistor.

[0199] 2) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat petri dish, and cured at 80°C for 12 hours. After complete curing, they were cut into long strips for use as flexible transfer substrates. PDMS was attached to the surface of the semiconductor film, quickly peeled off, and stretched by 0%, 25%, 50%, 75%, 100%, 125%, and 150% and then transferred to the unmodified silicon wafer surface (optical microscope images as shown in Figure 2). Figure 5 As shown). Then PDMS is applied to the surface of the semiconductor film, quickly peeled off, and stretched under 100% stress for 10, 100, 500, and 1000 times. The electrical properties are shown in Figure 2. Figure 8 , as shown in 12. By comparing with Example 1, it can be found that the electrical properties of the transistor device prepared by using the blended film without adding a compatibilizer as the semiconductor layer under different stretching conditions are much worse than those of the transistor device prepared after adding a compatibilizer. The mobility of the transistor device prepared from the blended film without adding a compatibilizer is significantly reduced in the horizontal and vertical directions under different strains within the strain range of 100%. On the other hand, the electrical properties of the transistor device prepared from the blended film without adding a compatibilizer are significantly reduced in the vertical and parallel stretching directions after 1000 cycles of stretching under 100% strain. Therefore, by comparing the electrical properties of Example 1 and Comparative Example 1, it can be found that the transistor prepared by adding a compatibilizer is significantly superior to the transistor without adding a compatibilizer in terms of electrical and mechanical properties, which makes the compatibilizer have important research value for the performance of transistor devices.

[0200] Example 2

[0201] In this embodiment, based on the "compatibilizer" PTIIGTVT-SI, the blended polymer semiconductor is PDPPTT, and the blended elastomeric polymer is SEBS, and the structure is as follows:

[0202]

[0203] The polymer semiconductor used (also the conjugated polymer used as the semiconductor segment in PTIIGTVT-SI) PDPPTT has a molecular weight of 50 kDa / mol; SEBS used is H1221 (from Asahi Kasei).

[0204] The blended film based on "compatibilizer" PTIIGTVT-SI, polymer semiconductor PDPPTT and SEBS was prepared by the following method:

[0205] 1. Preparation of "Compatibilizer" PTIIGTVT-SI (Compared with PDVT-SI, the intermediate bridging aromatic group of PTIIGTVT-SI is replaced by benzene from thiophene, and styrene is replaced by p-methylstyrene)

[0206] 1) The target polymer is capped in an inert atmosphere, and appropriate amounts of the capping compound 4-(3-bromopropyl)phenyltrimethyltin (2.68 mg), the polymer PTIIGTVT (200 mg), the catalyst tri(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3](0.4 mg) and the ligand tri(o-methylphenyl)phosphine P-(o-tol)3(1.2 mg) and 3 ml of ultra-dry chlorobenzene are weighed in a 10 ml Schlenk reaction tube and reacted at 125° C. for 24 hours; 2) The polymer after the reaction is precipitated in methanol, filtered, extracted, dried, and weighed to obtain the capped conjugated polymer PTIIGTVT-TP;

[0207] The structural formula is as follows:

[0208]

[0209] 3) Add 20 ml of anhydrous toluene, 40 ul of anhydrous tetrahydrofuran, 1.85 ml of anhydrous p-methylstyrene, and then add 0.08 mol of 0.1 M initiator n-butyl lithium in an inert atmosphere to obtain a red reaction solution, and react at 50° C. for 1 hour;

[0210] 4) adding anhydrous isoprene (9.6 ml, 96 mmol) dropwise to the reaction solution in step 3), and reacting at 50° C. for 2 hours to obtain a reaction solution containing an elastomer segment polymer;

[0211] 5) In anhydrous and oxygen-free atmosphere, the blocked conjugated polymer PTIIGTVT-TP (40 mg) was completely dissolved in 50 ml of anhydrous toluene, and then 12 ml of the reaction solution in step 4) was quickly added to the toluene solution containing PTIIGTVT-TP according to the designed ratio, and the reaction was carried out at 75° C. for 6 hours;

[0212] 6) After the reaction is completed, cool to room temperature, add 2 ml of methanol to the reaction bottle and stir for 30 minutes, then add 2 ml of dilute hydrochloric acid, and extract three times with dichloromethane and deionized water, and spin dry to obtain a crude product;

[0213] 7) Separating and purifying the crude product by column chromatography, non-polar polystyrene-isoprene can be eluted by column chromatography, the eluent is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to petroleum ether: dichloromethane = 1:1, v / v, so that the target product - block copolymer "compatibilizer" is separated;

[0214] 8) The target product mixed with silica gel is taken out, washed with tetrahydrofuran, filtered to remove the silica gel, and then the obtained mixed solution is spin-dried to obtain a pure block copolymer "compatibilizer", namely PTIIGTVT-SI; GPC test of THF phase at room temperature: Mn molecular weight = 81.8 kDa, Mw molecular weight = 85.3 kDa, PDI = 1.04. In the compatibilizer PTIIGTVT-SI, n is 44, a is 62, and b is 372. 1 H NMR (400MHz): δ (ppm) 7.84-7.75 (m, 8H), 7.28-7.12 (m, 15H), 7.11-7.08 (br, 4H), 7.02-6.98 (m, 3H), 6.61-6.56 ( m,4H),5.09(dq,12H),4.71(dd,8H),3.36(d,4H),2.01-1.97(m,52H),1.59-1.27(m,48H),0.92-0.72(br,18H).

[0215] 2. Preparation of blended films

[0216] 9) Weigh 5mg PDPPTT and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS. Then prepare a 10mg / ml chlorobenzene solution of compatibilizer, take different amounts of compatibilizer solution and add it to the above solution to prepare a final compatibilizer ratio of 0.1%, 1%, 3%, 5%, and 10%. In an atmospheric atmosphere, heat the solution on a hot plate at 75°C for 1h and stir continuously until it is completely dissolved. After the glue machine rotates at 500rpm on the OTS-modified silicon wafer for 5s, it rotates at 4000rpm for 60s to prepare a semiconductor film. After the preparation is completed, it is placed on a hot plate at 150°C for annealing for 30min to further improve the stacking and increase the mobility. Then evaporate gold as the source and drain electrodes to construct an organic field effect transistor.

[0217] 10) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat petri dish, cured at 80°C for 12 hours, and cut into long strips for use after complete curing. As a flexible transfer substrate, PDMS was used to adhere to the surface of the semiconductor film, quickly peeled off, and transferred to the unmodified silicon wafer surface after stretching 0%, 25%, 50%, 75%, and 100%. PDMS was then used to adhere to the surface of the semiconductor film, quickly peeled off, and stretched under 100% stress for 10, 100, 500, and 1000 cycles. The results show that the blended film exhibits excellent electrical and mechanical properties when used as a semiconductor layer in transistor devices. In terms of electrical properties, the mobility of transistor devices prepared by blended thin films remains unchanged in the vertical direction under different strains within the range of 100% strain, and the mobility does not decrease after the film is released, and there is a significant increase in the parallel direction under different strains within the range of 100% strain, and the mobility remains unchanged after the film is released. On the other hand, after 100% strain, the electrical properties of transistor devices made of blended thin films are very stable and remain unchanged in the vertical and parallel stretching directions after cyclic stretching for 1,000 times.

[0218] Comparative Example 2

[0219] In order to more clearly demonstrate the improvement and optimization of the device performance by the "compatibilizer", Comparative Example 2 was compared and analyzed with Example 2, wherein no "compatibilizer" was added in Comparative Example 2, and all other aspects such as preparation and testing were the same as Example 2.

[0220] In this comparative example, based on the conjugated polymer PDPPTT, the blended elastomeric polymer is SEBS, and the structure is as follows:

[0221]

[0222] The molecular weight of the conjugated polymer PDPPTT used was 50 kDa / mol; the SEBS used was H1221 (from Asahi Kasei).

[0223] The blended film based on conjugated polymer PDPPTT and SEBS was prepared by the following method:

[0224] 1. Preparation of blended films

[0225] 1) Weigh 5mg PDPPTT and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS. In an atmospheric atmosphere, place the solution on a hot plate at 75°C for 1h and stir continuously until it is completely dissolved. The gelator rotates on the OTS-modified silicon wafer at 500rpm for 5s, and then rotates at 4000rpm for 60s to prepare a blended film. After preparation, place it on a hot plate at 150°C for annealing for 30min to further improve stacking and increase mobility. Then evaporate gold as the source and drain electrodes to construct an organic field-effect transistor.

[0226] 2) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat culture dish, cured at 80°C for 12 hours, and cut into long strips for use after complete curing. As a flexible transfer substrate, PDMS was used to adhere to the surface of the semiconductor film, quickly peeled off, stretched 0%, 25%, 50%, 75%, and 100%, and then transferred to the surface of the unmodified silicon wafer. PDMS was then used to adhere to the surface of the semiconductor film, quickly peeled off, stretched under 100% stress, and cyclically stretched 10 times, 100 times, 500 times, and 1000 times. Among them, the electrical properties such as Fig.14 As shown. By comparison with Example 2, it can be found that the transistor device prepared by using the blended film without adding a compatibilizer as the semiconductor layer is much worse in electrical and mechanical properties than the transistor device prepared after adding a compatibilizer. In terms of electrical performance, the mobility of the transistor device prepared by the blended film without adding a compatibilizer is greatly reduced in the horizontal and vertical directions under different strains within the range of 100% strain. On the other hand, the electrical performance of the transistor device prepared by the blended film without adding a compatibilizer is significantly reduced in the vertical and parallel stretching directions after 1000 cycles of stretching under 100% strain. Therefore, by comparing the electrical and mechanical properties of Example 2 and Comparative Example 2, it can be found that the transistor prepared by adding a compatibilizer is significantly better than the transistor without adding a compatibilizer in terms of electrical and mechanical properties.

[0227] Example 3

[0228] In this embodiment, based on the "compatibilizer" PNDITVT-SI, the blended polymer semiconductor is N2200, and the blended elastomeric polymer is SEBS, and the structure is as follows:

[0229]

[0230] The polymer semiconductor used (also the conjugated polymer used as the semiconductor segment in PNDITVT-SI) N2200 has a molecular weight of 36 kDa / mol; SEBS used is H1221 (Asahi Kasei).

[0231] The blended film based on "compatibilizer" PNDITVT-SI, polymer semiconductor N2200 and SEBS was prepared by the following method:

[0232] 1. Preparation of "Compatibilizer" PNDITVT-SI (Compared with PDVT-SI, the intermediate bridging aromatic group of PNDITVT-SI is replaced by dithiophene from thiophene, and styrene is replaced by p-chlorostyrene)

[0233] 1) The target polymer was capped in an inert atmosphere. Appropriate amounts of the capping compound 5-(3-bromopropyl)thiophene[3,2-b]-2-yl)trimethyltin (3.12 mg), polymer PNDITVT (200 mg), catalyst tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3] (0.4 mg) and ligand tris(o-methylphenyl)phosphine P-(o-tol)3 (1.2 mg) and 3 ml of ultra-dry chlorobenzene were weighed in a 10 ml Schlenk reaction tube and reacted at 125° C. for 24 hours.

[0234] 2) The polymer after the reaction is precipitated in methanol, filtered, extracted, dried, and weighed to obtain a capped conjugated polymer PNDITVT-TP; the structural formula is shown below:

[0235]

[0236] 3) Add 20 ml of anhydrous toluene, 40 ul of anhydrous tetrahydrofuran, 1.85 ml of anhydrous p-chlorostyrene, and then add 0.08 mol of 0.1 M initiator n-butyl lithium in an inert atmosphere to obtain a red reaction solution, and react at 50° C. for 1 hour;

[0237] 4) adding anhydrous isoprene (9.6 ml, 96 mmol) dropwise to the reaction solution in step 6), and reacting at 50° C. for 2 hours to obtain a reaction solution containing an elastomer segment polymer;

[0238] 5) In anhydrous and oxygen-free atmosphere, the terminal substituted conjugated polymer PNDITVT-TP (40 mg) was completely dissolved in 50 ml of anhydrous toluene, and then 12 ml of the reaction solution in step 4) was quickly added to the toluene solution containing PNDITVT-TP according to the designed ratio, and the reaction was carried out at 75° C. for 6 hours;

[0239] 6) After the reaction is completed, cool to room temperature, add 2 ml of methanol to the reaction bottle and stir for 30 minutes, then add 2 ml of dilute hydrochloric acid, and extract three times with dichloromethane and deionized water, and spin dry to obtain a crude product;

[0240] 7) Separating and purifying the crude product by column chromatography, non-polar polystyrene-isoprene can be eluted by column chromatography, the eluent is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to petroleum ether: dichloromethane = 1:1, v / v, so that the target product - block copolymer "compatibilizer" is separated;

[0241] 8) The target product mixed with silica gel is taken out, washed with tetrahydrofuran, filtered to remove the silica gel, and then the obtained mixed solution is spin-dried to obtain a pure block copolymer "compatibilizer", namely PNDITVT-SI; GPC test of THF phase at room temperature: Mn molecular weight = 76.3 kDa, Mw molecular weight = 81.6 kDa, PDI = 1.07. In the compatibilizer PNDITVT-SI, n is 35, a is 78, and b is 468. 1 H NMR (400MHz): δ (ppm) 8.90-8.85 (s, 2H), 7.31-7.26 (m, 6H), 7.21-7.18 (s, 1H), 7.02-6.98 (m, 4H), 5.20 (s, 1H),5.09(dq,12H),4.71(dd,8H),3.50(d,4H),2.12-1.96(m,8H),1.59-1.27(m,16H),0.92-0.72(br,6H).

[0242] 2. Preparation of blended films

[0243] 9) Weigh 5mg N2200 and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS, then prepare a 10mg / ml chlorobenzene solution of compatibilizer, take different amounts of compatibilizer solution and add it to the above solution, and prepare the final compatibilizer ratio of 0.1%, 1%, 3%, 5%, and 10%. In an atmospheric atmosphere, heat the solution on a hot plate at 75°C for 1h, and stir continuously until it is completely dissolved. After the homogenizer rotates at 500rpm on the OTS-modified silicon wafer for 5s, it rotates at 4000rpm for 60s to prepare the semiconductor film. After the preparation is completed, it is placed on a hot plate at 150°C for annealing for 30min to further improve the stacking and increase the mobility.

[0244] 10) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat petri dish, cured at 80°C for 12 hours, and cut into long strips for use after complete curing. As a flexible transfer substrate, PDMS was used to adhere to the surface of the semiconductor film, quickly peeled off, and transferred to the unmodified silicon wafer surface after stretching 0%, 25%, 50%, 75%, and 100%. PDMS was then used to adhere to the surface of the semiconductor film, quickly peeled off, and stretched under 100% stress for 10, 100, 500, and 1000 cycles. The results show that the blended film exhibits excellent electrical and mechanical properties when used as a semiconductor layer in transistor devices. In terms of electrical properties, the mobility of transistor devices prepared by blended thin films remains unchanged in the vertical direction under different strains within the range of 100% strain, and the mobility does not decrease after the film is released, and there is a significant increase in the parallel direction under different strains within the range of 100% strain, and the mobility remains unchanged after the film is released. On the other hand, after 100% strain, the electrical properties of transistor devices made of blended thin films are very stable and remain unchanged in the vertical and parallel stretching directions after cyclic stretching for 1,000 times.

[0245] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

[0246] Comparative Example 3

[0247] In order to more clearly demonstrate the improvement and optimization of the device performance by the "compatibilizer", Comparative Example 3 was compared and analyzed with Example 3, wherein no "compatibilizer" was added in Comparative Example 3, and all other aspects such as preparation and testing were the same as Example 3.

[0248] In this comparative example, based on the conjugated polymer N2200, the blended elastomeric polymer is SEBS, and the structure is as follows:

[0249]

[0250] The molecular weight of the conjugated polymer PDPPTT used was 36 kDa / mol; the SEBS used was H1221 (from Asahi Kasei).

[0251] The blended film based on conjugated polymer N2200 and SEBS was prepared by the following method:

[0252] 1. Preparation of blended films

[0253] 1) Weigh 5mg PDPPTT and 5mg SEBS into a pre-washed glass bottle, add 1ml chlorobenzene, and finally prepare a 10mg / mL solution containing 50% SEBS. In an atmospheric atmosphere, place the solution on a hot plate at 75°C for 1h and stir continuously until it is completely dissolved. The gelator rotates on the OTS-modified silicon wafer at 500rpm for 5s, and then rotates at 4000rpm for 60s to prepare a blended film. After preparation, place it on a hot plate at 150°C for annealing for 30min to further improve stacking and increase mobility. Then evaporate gold as the source and drain electrodes to construct an organic field-effect transistor.

[0254] 2) PDMS precursor (prepolymer) and Dow Corning SYLGARD 184 curing agent were mixed evenly at a mass ratio of 12:1, poured into a flat culture dish, cured at 80°C for 12 hours, and cut into long strips for use after complete curing. As a flexible transfer substrate, PDMS was used to adhere to the surface of the semiconductor film, quickly peeled off, stretched 0%, 25%, 50%, 75%, and 100%, and then transferred to the surface of the unmodified silicon wafer. PDMS was then used to adhere to the surface of the semiconductor film, quickly peeled off, stretched under 100% stress, and cyclically stretched 10 times, 100 times, 500 times, and 1000 times. Among them, the electrical properties such as Fig.16 As shown. By comparison with Example 2, it can be found that the transistor device prepared by using the blended film without adding a compatibilizer as the semiconductor layer is much worse in electrical and mechanical properties than the transistor device prepared after adding a compatibilizer. In terms of electrical performance, the mobility of the transistor device prepared by the blended film without the addition of a compatibilizer is greatly reduced in the horizontal and vertical directions under different strains within the range of 100% strain. On the other hand, the electrical performance of the transistor device prepared by the blended film without the addition of a compatibilizer is significantly reduced in the vertical and parallel stretching directions after 1000 cycles of stretching under 100% strain. Therefore, by comparing the electrical and mechanical properties of Example 3 and Comparative Example 3, it can be found that the transistor prepared by adding a compatibilizer is significantly better than the transistor without the addition of a compatibilizer in terms of electrical and mechanical properties.

Claims

1. A block copolymer "compatibilizer" comprising semiconductor and elastomer segments, the structural formula of which is shown in Formula 1: In the structural formula 1, the semiconductor fragment refers to a conjugated polymer fragment polymerized by coupling reaction; wherein, A1 and A2 monomers are independently selected from any structure of formula 2 and structural units with similar functions developed on the basis of this structure; R in any monomer in Formula 2 is independently selected from any one of the following: hydrogen, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, an alkoxy group or an alkylthio side chain; n in the semiconductor segment is the number of repeating units A1-A2, and the value of n is an integer ranging from 10 to 1000; In the structural formula 1, the Ar unit is a group that terminates the semiconductor; In the structural formula 1, the elastomer segment is polymerized by a flexible unit and a rigid unit; wherein R1, R2, R3, R4, R5, R6, and R7 are each independently selected from hydrogen, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, an alkoxy group, or an alkylthio group; In the elastomer segment, b:a is selected from any value in the ratio range of 30:1 to 1:5; In the structural formula 1, c is an integer of 1-20; In the structural formula 1, the content of the elastomer segment accounts for 20-80wt% of the total mass of the "compatibilizer".

2. The block copolymer "compatibilizer" comprising semiconductor and elastomer segments according to claim 1, characterized in that: The semiconductor fragments include but are not limited to: diketopyrrolopyrrole conjugated polymers, isoindigo conjugated polymers, naphthalimide conjugated polymers, and perylene imide conjugated polymers; And / or, the Ar unit includes but is not limited to: a thiophene group, a thienothiophene group, a dithiophene group, a benzene group, a diphenyl group, a naphthyl group, an anthracenyl group, etc.; and / or, in the elastomer segment, the ratio of b:a is 6:1; and / or, in the elastomer segment, R1, R2, R4, and R5 are all hydrogen; and / or, in the elastomer segment, R3 is hydrogen, halogen or C1-C20 alkyl; and / or, in the elastomer segment, R6 is hydrogen and R7 is methyl; and / or, in the formula 2, R are each independently selected from any one of the following groups: substituted or unsubstituted alkyl, substituted or unsubstituted aryl, alkoxy or alkylthio; preferably, R are each independently selected from any one of the following groups: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, n-hexyl, n-heptyl, n-octyl, isooctyl, n-nonyl, phenyl, fluorophenyl, bromophenyl, chlorophenyl, o-tolyl, p-tolyl, m-tolyl, o-ethylphenyl, p-ethylphenyl, m-ethylphenyl, o-isopropylphenyl, p-isopropylphenyl, m-isopropylphenyl, 1-naphthyl, 2-naphthyl, methylthio, ethylthio, propylthio, butylthio, pentylthio, hexylthio, heptylthio, octylthio, nonylthio, decylthio, methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, nonyloxy or decyloxy.

3. The block copolymer "compatibilizer" comprising semiconductor and elastomer segments according to claim 1 or 2, characterized in that: The structural formula of the compatibilizer shown in Formula 1 is selected from any of the following structures:

4. A method for preparing a block copolymer "compatibilizer" comprising semiconductor and elastomer segments as described in any one of claims 1 to 3, comprising the following steps: S1, polymerizing monomer A1 and monomer A2 through a coupling reaction to synthesize a semiconductor polymer; S2, capping the semiconductor polymer obtained in step S1 through a metal coupling reaction; the metal coupling reaction is Stille reaction or Suzuki reaction; S3, obtaining an elastomer segment through anionic polymerization; S4, further polymerizing the end-capped semiconductor polymer obtained in step S2 and the elastomer fragment obtained in step S3 to finally obtain the target product "compatibilizer"; in, The monomers A1 and A2 used in S1 are independently selected from any monomer structure shown in Formula 2 as claimed in claim 1 and structural units with similar functions developed on the basis of the monomer structure.

5. The method for preparing PDVT-SI according to claim 4, wherein the synthetic route (A) is as follows, comprising the following steps: (a1) weighing a certain amount of brominated monomer and tin compound monomer, catalyst and ligand in an inert atmosphere, and then adding a reaction solvent to mix, to obtain a mixed reaction solution; performing three Freeze-Pump-Thaw operations in liquid nitrogen under anhydrous and oxygen-free conditions, i.e., a three-step cycle of freezing-vacuuming-thawing, to remove water and oxygen in the solvent of the reaction bottle; (a2) heating and stirring the mixed solution under anhydrous and oxygen-free conditions to react; (a3) After the reaction is completed, the mixture is cooled to room temperature, a methanol solution containing a small amount of hydrochloric acid is added to quench the reaction, and then Soxhlet extraction is performed with methanol, acetone and n-hexane in sequence, and the precipitated polymer is obtained by filtering or suction filtration; pure chlorobenzene or chloroform is added again to extract the polymer by a Soxhlet extractor to obtain a conjugated polymer as a semiconductor fragment, i.e., product c in reaction route (A); (a4) weighing appropriate amounts of the end-capping compound, the conjugated polymer obtained in step (3), the catalyst and the ligand, and subjecting the conjugated polymer obtained in step (a3) ​​to an end-capping reaction in an inert atmosphere, wherein the end-capping reaction is a Stille reaction; (a5) subjecting the reaction system obtained after the reaction to Soxhlet extraction in methanol, acetone and n-hexane in turn, and then filtering or suction filtration to obtain a precipitated polymer; re-adding chlorobenzene or trichloroethane to extract the polymer through a Soxhlet extractor to obtain a capped conjugated polymer, i.e., product d in reaction route (A); (a6) adding a certain amount of anhydrous toluene, anhydrous tetrahydrofuran, and anhydrous styrene in an inert atmosphere, and then adding a certain amount of 0.1 M initiator n-butyl lithium to obtain a red reaction solution, and heating the reaction at 40-60° C. for 0.5 to 2 hours; (a7) adding anhydrous isoprene dropwise to the reaction solution in step (a6), the reaction solution turns slightly yellow, and heating the reaction solution at 40-60° C. for 1 to 3 hours to obtain a reaction system containing an elastomer segment polymer, i.e., product e in reaction route (A); (a8) in anhydrous and oxygen-free atmosphere, after completely dissolving the capped conjugated polymer obtained in step (a5) in toluene, adding the polymer to the reaction system containing the elastomer segment in step (a7) according to the designed feed ratio, and heating the reaction at 50-100° C. for 1 to 12 hours; (a9) After the reaction is completed, cool to room temperature, add a small amount of methanol to quench, stir for 10-90 minutes, add an appropriate amount of dilute hydrochloric acid, and extract with dichloromethane and deionized water for at least three times, and spin dry to obtain a crude product; Furthermore, the method also includes the step of separating and purifying the obtained crude product, which is specifically as follows: (a10) separating and purifying the crude product by column chromatography. Non-polar polystyrene-isoprene can be eluted by column chromatography to separate the target product. (a11) taking out the target product mixed with silica gel, washing it with tetrahydrofuran, filtering to remove the silica gel, and then spinning the obtained mixed solution to dryness to obtain a pure polymer "compatibilizer"; Further, in the step (a1), the brominated monomer is selected from: 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione; the tin-substituted monomer is selected from: (E)-1,2-bis(5-(trimethyltinyl)thiophene-2-yl)ethylene; In the step (a1), the molar ratio of the brominated monomer to the tin-substituted monomer is 1:1-1:1.05 (the brominated monomer is slightly less than the tin-substituted monomer); In the step (a1), the catalyst is one of tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetone)palladium(dba)2. Preferably, the catalyst tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3] is selected, and the amount of the catalyst is 1-5% of the molar amount of the tin-substituted monomer in the reaction system; In the step (a1), the ligand is tri(o-methylphenyl)phosphine P-(o-tol)3; one of triphenylphosphine PPh3 and tri-tert-butylphosphine P(t-Bu)3. Preferably, the ligand tri(o-methylphenyl)phosphine P-(o-tol)3 is selected, and the molar ratio of the amount of the ligand to the amount of the catalyst is 2:1-10:1; In the step (a1), the reaction solvent is one of chlorobenzene, toluene, xylene, dichlorobenzene, trimethylbenzene, trichlorobenzene, chloronaphthalene, chlorotoluene, chloroxylene, chloroethylbenzene and the like. Preferably, chlorobenzene is selected as the reaction solvent; Furthermore, in the step (a2), the reaction temperature is 115-130° C., and the reaction time is 48-72 hours; Furthermore, in the step (a3), the quenching reaction is stirred for 1-3 hours, and Soxhlet extraction is performed with methanol, acetone, and n-hexane in sequence for 12-24 hours; Furthermore, in the step (a4), the added end-capping compound has the structural formula The molar ratio of the end-capping compound to the conjugated polymer is 1:1-1:1.05; In the step (a4), the catalyst is one of tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetonepalladium)Pd(dba)2. Preferably, the catalyst tetrakis(triphenylphosphine)palladium Pd(PPh3)4 is selected, and the amount of the catalyst used is 1-5% of the molar amount of the end-capping compound in the reaction system; In the step (a4), the ligand is tri(o-methylphenyl)phosphine P-(o-tol)3; one of triphenylphosphine PPh3 and tri-tert-butylphosphine P(t-Bu)3. Preferably, the ligand tri(o-methylphenyl)phosphine P-(o-tol)3 is selected, and the molar ratio of the amount of the ligand to the amount of the catalyst is 2:1-10:1; In the step (a4), the reaction is carried out in a reaction solvent, and the reaction solvent is one of solvents such as chlorobenzene, toluene, xylene, dichlorobenzene, trimethylbenzene, trichlorobenzene, chloronaphthalene, chlorotoluene, chloroxylene, and chloroethylbenzene. Preferably, chlorobenzene is selected as the reaction solvent; The reaction conditions of the end-capping reaction are heating the reaction at a temperature range of 100°C to 130°C for 10-60 hours; preferably, the reaction is carried out at 125°C for 24 hours; Furthermore, in the step (a5), the extraction time is 12-24 hours; Furthermore, in the step (a6), the amount of anhydrous tetrahydrofuran added is 0.5-20 times the molar amount of n-butyl lithium, and the amount of anhydrous toluene added is 5-20 times the molar amount of anhydrous styrene; the amount of n-butyl lithium added is 1 / 200 of the molar amount of styrene; Furthermore, in the step (a6), preferably, the reaction is heated at 50° C. for 1 hour; Furthermore, in the step (a7), the molar amount of the added isoprene needs to be regulated according to the molar amount of styrene in the reaction solution of step (s6), and the feeding molar ratio of isoprene to styrene is 1:1-1:100, preferably, the feeding molar ratio is 1:5-1:10; Furthermore, in the step (a7), preferably, the reaction is heated at 50° C. for 2 hours; Further, in the step (a8), the molar amount of the end-capped conjugated polymer does not exceed 50% of the total molar amount of the end-capped conjugated polymer and the elastomer segment-containing polymer; Furthermore, in the step (a8), preferably, the reaction is carried out at 75° C. for 6 hours; Furthermore, in the step (a10), the eluent used in the column chromatography is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to a mixed solvent of petroleum ether and dichloromethane (petroleum ether: dichloromethane = 1:1, v / v); Furthermore, in the step (a11), the silica gel mixture is washed with tetrahydrofuran for 3 times. Ultrasonic treatment is prohibited during this process, and the silica gel must be completely removed during the filtration process.

6. The method for preparing PDVT-SI according to claim 4, wherein the synthetic route (B) is as follows, comprising the following steps: (b1) weighing a certain amount of brominated monomer and borate end-capping compound, catalyst and base in an inert atmosphere, and then adding a reaction solvent to mix to obtain a mixed reaction solution, and performing three Freeze-Pump-Thaw operations in liquid nitrogen under anhydrous and oxygen-free conditions, i.e., a three-step cycle of freezing-vacuuming-thawing, to remove oxygen from the solvent in the reaction bottle; (b2) heating and stirring the mixed solution under an inert gas atmosphere to react; (b3) After the reaction is completed, the mixture is cooled to room temperature, and then Soxhlet extraction is performed with methanol, acetone and n-hexane in sequence, and the precipitated polymer is obtained by filtering or suction filtration; pure chlorobenzene or chloroform is added again to extract the polymer with a Soxhlet extractor to obtain a conjugated polymer as a semiconductor fragment, i.e., product c in reaction route (B); (b4) weighing appropriate amounts of the end-capping compound, the conjugated polymer obtained in step (3), a catalyst and a base, and performing an end-capping reaction on the target conjugated polymer obtained in step (b3) in an inert atmosphere, wherein the end-capping reaction is a Suzuki reaction; (b5) extracting the reaction system obtained after the reaction in methanol, acetone and n-hexane in turn, and then filtering or suction filtration to obtain a crude polymer after end-capping; re-adding chlorobenzene or trichloroethane to extract the polymer through a Soxhlet extractor to obtain an end-capped conjugated polymer, i.e., product d in reaction route (B); (b6) adding a certain amount of anhydrous toluene, anhydrous tetrahydrofuran, and anhydrous styrene in an inert atmosphere, and then adding a certain amount of 0.1 M initiator n-butyl lithium to obtain a red reaction solution, and heating the reaction at 40-60° C. for 0.5 to 2 hours; (b7) adding anhydrous isoprene dropwise to the reaction solution in step (b6), the reaction solution turns slightly yellow, and heating the reaction solution at 40-60° C. for 1 to 3 hours to obtain a reaction system containing an elastomer segment polymer; (b8) in anhydrous and oxygen-free atmosphere, after completely dissolving the capped conjugated polymer obtained in step (b5) in toluene, adding the end-capped conjugated polymer obtained in step (b5) into the reaction system containing the elastomer segment polymer in step (b7) according to the designed feed ratio, and heating the reaction at 50-100° C. for 1 to 12 hours; (b9) After the reaction is completed, cool to room temperature, add a small amount of methanol to quench, stir for 10-90 minutes, add an appropriate amount of dilute hydrochloric acid, and extract with dichloromethane and deionized water for at least three times, and spin dry to obtain a crude product; Furthermore, the method further comprises the step of separating and purifying the obtained crude product, which is specifically as follows: (b10) separating and purifying the crude product by column chromatography, wherein the non-polar polystyrene-isoprene can be eluted by column chromatography, thereby separating the target product; (b11) taking out the target product mixed with silica gel, washing it with tetrahydrofuran, filtering to remove the silica gel, and then spinning the obtained mixed solution to dryness to obtain a pure polymer "compatibilizer"; Further, in the step (b1), the brominated monomer is selected from: 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione; the borate ester monomer is selected from: (E)-1,2-bis(5-(4,4,5,5-tetramethyl)-1,3,2-dioxaborolane-2-yl)thiophenevinylthiophene; In the step (b1), the molar ratio of the brominated monomer to the borate ester monomer is 1:1-1:1.05; In the step (b1), the catalyst is one of 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride PdCl2(dppf), tetrakis(triphenylphosphine)palladium Pd(PPh3)4, tris(dibenzylideneacetone)dipalladium(0)[Pd2(dba)3], palladium acetate Pd(OAc)2, and bis(dibenzylideneacetonepalladium Pd(dba)2. Preferably, the catalyst tetrakis(triphenylphosphine)palladium Pd(PPh3)4 is selected, and the amount of the catalyst is 1-5% of the molar amount of the borate end-capping compound in the reaction system; In the step (b1), the base is one of lithium carbonate, potassium carbonate, sodium carbonate, cesium carbonate, potassium acetate, tetrabutylammonium fluoride, cesium fluoride, potassium fluoride, and potassium phosphate, preferably potassium carbonate; In the step (b1), the reaction solvent is one of a solvent system such as a toluene and water mixture system, a toluene and tetrahydrofuran mixture system, dioxane, N,N-dimethylformamide, etc. Preferably, a toluene and water mixture system is selected as the reaction solvent; Furthermore, in the step (b2), the reaction temperature is 80-130° C., and the reaction time is 24-72 hours; Furthermore, in the step (b3), the reaction is quenched and stirred for 1-3 hours, and Soxhlet extraction is performed with methanol, acetone, and n-hexane in sequence for 12-24 hours; Furthermore, if the conjugated polymer as the semiconductor fragment obtained in step (b3) is commercially available, it can also be directly used as a raw material to start the preparation from step (b4); Furthermore, in the step (b4), the added end-capping compound has the structural formula The molar ratio of the end-capping compound to the conjugated polymer is 1:1-1:1.05; In the step (b4), the catalyst is tetrakis(triphenylphosphine)palladium Pd(PPh3)4, and the amount of the catalyst is 1-5% of the molar amount of the borate end-capped compound in the reaction system. Too much catalyst is not conducive to the increase of molecular weight; In the step (b4), the base may be one of lithium carbonate, potassium carbonate, sodium carbonate, cesium carbonate, potassium acetate, tetrabutylammonium fluoride, cesium fluoride, potassium fluoride, and potassium phosphate, preferably potassium carbonate; In the step (b4), the reaction is carried out in a reaction solvent, and the reaction solvent is one of a solvent system such as a toluene and water mixture system, a toluene and tetrahydrofuran mixture system, dioxane, N,N-dimethylformamide, etc. Preferably, a toluene and water mixture system is selected as the reaction solvent; In the step (b4), the end-capping reaction is carried out under the conditions of heating at a temperature range of 80°C to 130°C for 10-60 hours; preferably, at 100°C for 48 hours; Furthermore, in the step (b5), the extraction time is 12-24 hours; Furthermore, in the step (b6), the amount of anhydrous tetrahydrofuran added is 0.5-20 times the molar amount of n-butyl lithium, the amount of anhydrous toluene added is 5-20 times the molar amount of anhydrous styrene; the amount of n-butyl lithium added is 1 / 200 of the molar amount of styrene; Furthermore, in the step (b6), preferably, the reaction is heated at 50° C. for 1 hour; Furthermore, in the step (b7), the molar amount of the added isoprene needs to be regulated according to the molar amount of styrene, and the feeding molar ratio of isoprene to styrene is 1:1-1:100, preferably, the feeding molar ratio is 1:5-1:10; Further, in step (b8), the molar amount of the capped conjugated polymer does not exceed 50% of the total molar amount of the capped conjugated polymer and the elastomer segment-containing polymer; Furthermore, in step (b10), the eluent used in the column chromatography is a mixed solvent of petroleum ether and dichloromethane, and the polarity gradually increases from pure petroleum ether to a mixed solvent of petroleum ether and dichloromethane (petroleum ether: dichloromethane = 1:1, v / v); Furthermore, in step (b11), the silica gel mixture is washed with tetrahydrofuran for 3 times. Ultrasonic treatment is prohibited during this process, and the silica gel must be completely removed during the filtration process.

7. Use of the block copolymer "compatibilizer" comprising semiconductor and elastomer segments as claimed in any one of claims 1 to 3 in the preparation of flexible and stretchable field effect transistors.

8. A flexible and stretchable field effect transistor, the active layer of which comprises a block copolymer "compatibilizer" comprising semiconductor and elastomer segments as claimed in any one of claims 1 to 3; Furthermore, the active layer also includes a polymer semiconductor and an elastomer; Preferably, the added amount of the compatibilizer is 0.01%-40% of the total mass of the polymer semiconductor and the elastomer, preferably 1%-5%.

9. The method for preparing the flexible and stretchable field effect transistor according to claim 8, comprising the following steps: (a) firstly adding the block copolymer "compatibilizer" comprising semiconductor and elastomer segments as claimed in any one of claims 1 to 3 to a mixed solution of a polymer semiconductor and an elastomer, and preparing a blended semiconductor film on a substrate by spin coating; (b) preparing an elastic substrate for transferring the blended semiconductor film; (c) Using an elastic substrate, the blended semiconductor film is transferred and stretched with different forces, and then transferred to a target substrate again, and source and drain electrodes are evaporated to obtain the flexible and stretchable field effect transistor.

10. The preparation method according to claim 9, characterized in that: In the step (a), the polymer semiconductor and the elastomer are dissolved in chlorobenzene and heated to dissolve them to obtain a mixed solution; And / or, in the step (a), the polymer semiconductor is a PDVT-10 molecule, and the elastomer is SEBS; PDVT-10 and SEBS are physically blended in a certain ratio, and the mass ratios of PDVT-10:SEBS are 1:0, 3:1, 1:1, 3:7, and 1:9, respectively. Preferably, on the basis of the blending ratio of PDVT-10 and SEBS being 1:1, the compatibilizer is added, and the mass of the added compatibilizer is 0.1%-10% of the total mass of the PDVT-10 semiconductor polymer and the SEBS elastomer; And / or, in the step (a), the mass ratio of PDVT-10 to SEBS is 1:0, the spin coating speed of the other four ratios is 1500 rpm, and the other rotation speeds are 4000 rpm; the substrate selected is an OTS-modified silicon wafer; the evaporated metal is gold, which serves as the source and drain electrodes; And / or, in the step (b), the elastic substrate is PDMS, and its preparation includes mixing the PDMS precursor and Dow Corning SYLGARD184 curing agent at a mass ratio of 12:1, pouring into a glass culture dish, curing at 80° C. for 12 hours, and cutting into strips for later use; And / or, in the step (c), a PDMS substrate is attached to the film prepared by spin coating, quickly peeled off, and then placed on a stretching device, and the stretching forces include 0%, 25%, 50%, 75%, and 100%.